Pengaruh Skarifikasi dan Perendaman Giberelin Pada Perkecambahan Melon (Cucumis melo L.) : Melon, Skarifikasi, Giberellin - Rahmatika, Widyana; Fitriyah, Nur; Imadudin, Alfian; Mardiana, Yushi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
The aim of this research was to determine the effect of scarification, the effect of gibberellin soaking and to determine the interaction of the two treatments. The research was carried out on Jl. Diponegoro, Kayen Kidul, Kediri. With a height of 86 M above sea level. The research was carried out from July to October 2024. The research used a factorial Randomized Block Design consisting of 2 treatment factors with 8 treatment combinations and repeated 4 times. The first factor, scarification (F), consists of 2 types, F1 = Control (no treatment) and F2 = seed scarification. The second treatment factor, Gibberellin (G) consists of 4 levels, G1 = gibberellin 0 ppm, G2 = Gibberellin 20 ppm, G3 = Gibberellin 40 ppm and G4 = Gibberellin 40 ppm The parameters observed are the initial vegtative growth of melon, plant height (cm), and number of leaves (strands). The results of the research showed that there was an interaction between scarification treatment and gibberellin soaking on the parameters for observing plant height and number of leaves with the best treatment being F1G3.